Other Subordination Results for Fractional Integral Associated with Dziok Srivastava Operator - Alb Lupas Alina (Journal of Advances in Applied & Computational Mathematics, 2019)
In this paper we have discussed differential subordination properties associated with the fractional integral by using Dziok-Srivastava operator